Pig kahuna - Sattler, Jennifer Gordon (New York : Bloomsbury, 2011)
Fergus is afraid to go in the water, but he and his baby brother Dink find a surfboard while collecting treasures along the seashore.
Kirkus Starred
Publisher's Weekly
School Library Journal starred
Booklist, April 2011
Kirkus Starred, April 2011
Publisher's Weekly, March 2011
Keywords: Surfing -- Juvenile fiction; Swine -- Juvenile fiction; Pigs -- Fiction; Surfing -- Fiction; Pigs -- Fiction; Surfing -- Fiction; Picture books for children